Dukungan Suami dan Depresi Postpartum: Husband Support and Postpartum Depression - Annisa, Nurul Hikmah; Natalia, Omiati (Indonesian Journal of Midwifery (IJM), 2023)
This study aims to determine the relationship between a husband's support and postpartum depression in women. In this study, the hypothesis proposed is that there is a negative relationship between a husband's support and postpartum depression in women. The subjects of this study were postpartum women who were in the early adult age range who lived in Ungaran district. Social support is in the form of emotional support, the support award, instrumental support and informative support. The method used in this research is using qualitative exploratory study the two subjects who had a husband and wife with postpartum depression after giving birth first child with wife aged 21-28 years. Determination of the subjects in this study using purposive sampling technique and is located in several places according to the agreement of the subject and significant others. Data collection methods used were observation method using anecdotel record with the observation that social support indicators husband and interview methods are equipped with general guidance interview. The results showed that each subject provide social support her husband with different forms of support for marriage influenced by the subject. The number of subjects in this study was 50 people. The data collection tool used in this study is the Scale of Social Support and BDI. The data were analyzed using product moment analysis from Pearson with the results of the correlation (Ray) of -0.842 (p <0.01). Based on the results of data analysis, the research hypothesis is acceptable.   Abstrak Penelitian ini bertujuan untuk mengetahui hubungan antara dukungan suami dengan depresi pasca melahirkan pada wanita. Dalam penelitian ini dirumuskan suatu hipotesis yaitu ada hubungan negatif antara dukungan suami dengan depresi pasca melahirkan pada wanita. Dukungan sosial berupa dukungan emosional, dukungan penghargaan, dukungan instrumental dan dukungan informatif. Metode yang digunakan dalam penelitian ini adalah kualitatif eksploratif dengan dua subjek yang memiliki suami istri dengan depresi pasca melahirkan setelah melahirkan anak pertama dengan istri berusia 21-28 tahun. Penentuan subjek dalam penelitian ini menggunakan teknik purposive sampling dan berlokasi di beberapa tempat sesuai kesepakatan subjek dan orang terdekat. Metode pengumpulan data yang digunakan adalah metode observasi dengan menggunakan anecdotel record dengan observasi indikator dukungan sosial suami dan metode wawancara yang dilengkapi dengan pedoman umum wawancara. Hasil penelitian menunjukkan bahwa setiap subjek memberikan dukungan sosial kepada suaminya dengan bentuk dukungan pernikahan yang berbeda-beda dipengaruhi oleh subjek. Subjek penelitian ini adalah wanita pasca melahirkan yang berada pada rentang usia dewasa awal yang bertempat tinggal di kabupaten Ungaran. Alat pengumpul data yang digunakan dalam penelitian ini adalah Skala Dukungan Sosial dan BDI. Analisis data yang digunakan dalam penelitian ini dalah analisis product moment dari Pearson dengan hasil korelasi (Ray) sebesar -0,842 (p<0,01). Berdasarkan hasil analisis data, hipotesis penelitian ini dapat diterima